Experimental and kinetic modelling studies for the design of fixed bed methanol reactor over CuZA catalyst - Bagwan, Farahanaz M.; Dongapure, Pavan; Kulkarni, Amol A.; Vasireddy, Satyam Naidu (Chemical Engineering Research Design, 2024)
Direct conversion of CO 2 via hydrogenation to value-added chemicals is a vital approach for utilising CO 2 emitted into the atmosphere. In this paper, a critical analysis of reaction kinetic modelling studies is explored in a fixed bed reactor to improve methanol yield for different H 2 to CO 2 ratios by simulating a lab-scale reactor for adiabatic and isothermal conditions. The feed inlet temperature and pressure variations are applied to study the effect of both configurations on methanol production. The results show that the isothermal configuration yields 2.76% more methanol yield compared to the adiabatic reactor. The effect of H 2 to CO 2 molar ratios of 3, 6 and 9 on the performance of the catalyst and the influence of CO and CO 2 hydrogenation is investigated with model simulations. The overall methanol yield is increased from 19.03% to 36.41% with increase in H 2 to CO 2 molar ratio from 3 to 9. Experiments are performed using commercial copper-based catalyst for different temperatures of 210, 230 and 250 degrees C at a pressure of 40 bar for H 2 /CO 2 of 3 and GHSV of 720 h -1 as well as at optimal temperature of 250 degrees C and 50 bar with varying H 2 /CO 2 of 3, 6, 9 for 3 g and 6 g catalyst. The maximum methanol yield of 2.53% and space time yield of 13.59 mg/g cat .h is obtained at H 2 /CO 2 ratio of 9.
Keywords: CO2 conversion; CuZA catalyst; H2 toCO2 molar ratio; Kinetic modelling; Methanol

Power generation with negative CO2 emissions through bio-electricity with CCS using dry co-gasification of coal-biomass blends - Vasireddy, Satyam Naidu; Jayanti, Sreenivas (Clean Technologies and Environmental Policy, 2024)
Among the measures proposed for decarbonization of electricity generation, large reductions in CO2 emissions are possible by the adoption of bio-electricity with carbon dioxide capture and sequestration. In the present study, thermodynamic analysis of a thermal power plant that produces electricity through co-gasification of high-ash coal and Casuarina equisetifola (CE), a crop which grows along the Indian coastline, and which is not in competition with other agricultural crops for land and water use, is considered for integrated gasification combined cycle (IGCC) with CO2 capture via oxyfuel combustion and gasification technology. The integrated power plant layout includes the energy required for CO2 gasification of coal, biomass blended fuel, air separation to produce oxygen for oxyfuel combustion as well as for purification and compression of the flue gas up to 30 bar. Simulation results show that a net efficiency of 37% can be achieved using high-ash Indian coal and CE blends up to 30% of the latter. Synergetic effect of co-gasification components is observed in mass, molar and thermal energy flowrates for biomass blended fuel. With the help of CCS, CO2 emissions are reduced to 69.91 gCO(2)/kWh for 100% coal-based IGCC-CC plant and further to -21.69 gCO(2)/kWh (negative CO2 emissions) for 30% biomass blending, thus paving way for CO2-negative power generation.
Keywords: BECCS; Combustion; Dry co-gasification; IGCC-CC plant; Negative CO2 emissions; Oxyfuel; Thermodynamic analysis

Reaction kinetics for catalytic hydrogenation of quinoline to decahydroquinoline as liquid organic hydrogen carrier - Bagwan, Farahanaz M.; Kinage, Anil K.; Vasireddy, Satyam Naidu (International Journal of Hydrogen Energy, 2024)
The catalytic hydrogenation of quinoline to decahydroquinoline (DHQ) formation is studied for various parameters such as temperature, hydrogen pressure, reaction time, solvents, reactant-to-solvent ratio, and catalyst loading over 5%Pd loaded on alumina (Pd/Al2O3) to obtain optimal reaction conditions. The hydrogen uptake of quinoline in the liquid phase reaction using isopropylalcohol (IPA) is studied in an autoclave reactor. The optimum reaction parameters of 50 bar H2 pressure and 175oC with reactant to solvent ratio of 1:9 for reaction time of 5 h are observed. The effect of IPA solvent showed that hydrogen uptake of 6.91 wt% with complete hydrogenation of quinoline and DHQ yield of more than 99% is observed. The reaction kinetic model is developed for a simplified reaction mechanism and is simulated using the Markov Chain Monte Carlo (MCMC) simulation tool to predict the rate constants and the experimental observations are validated with the model predictions. The activation energy for quinoline hydrogenation to py-THQ formation is estimated to be 136.57 kJ/mol. It is envisaged that quinoline hydrogenation to pz-THQ is the rate-limiting step in the DHQ formation.
Keywords: Decahydroquinoline (DHQ); Hydrogen uptake; Liquid organic hydrogen carrier (LOHC); Markov chain Monte Carlo (MCMC) simulation; Thermal screening unit (TSU); tool

Evaluation of reaction kinetics for chemoselective hydrogenation of citral for intensification of citral intermediates using copper-based catalysts - Debtirtha, Banik; Kinage, Anil K.; Vasireddy, Satyam Naidu (Indian Chemical Engineer, 2025)
Citral intermediates’ formation kinetics is studied using non-noble metal catalyst (Cu/SiO2) to evaluate catalyst performance characteristics via chemoselective hydrogenation of citral. The catalyst is synthesised by the precipitation method and characterised using XRD, FESEM and BET surface area analyser. Hydrogenation experiments are carried out using an Autoclave reactor in the temperature range of 80–120°C, pressure range of 10–50 bar and for catalyst loadings of 0.5, 1 and 1.5 g. The intermediates product distribution comprises aldehyde and alcohol formation such as citronellal, nerol and citronellol formation. The performance of the Cu/SiO2 catalyst is evaluated using the parameters such as citral conversion, citronellol selectivity and yield as 96.96%, 95.30% and 92.30%, respectively under optimal conditions of 50 bar, 120°C and 1 g catalyst for the reaction time of 100 min. The absence of internal and external mass transfer limitations is verified using the Carberry number and Weisz-Prater modulus criterion. The intrinsic kinetics of the gas–liquid phase hydrogenation of citral is determined using the Langmuir–Hinshelwood-Hougen-Watson (LHHW) model for citral intermediates formation. The reaction kinetic parameters show that citronellol formation favours by the nerol route compared to citronellal conversion.

Experimental investigation and lumped kinetic modeling studies for upcycling of polyolefins - Kavade, Omkar G.; Dhepe, Paresh L.; Devi, Nandini R.; Vasireddy, Satyam Naidu (Journal of the Indian Chemical Society, 2025)
The present work discusses on comparative kinetic analysis of the pyrolysis of polypropylene (PP), high-density polyethylene (HDPE), and low-density polyethylene (LDPE) using sophisticated lumped models. Unlike many previous studies that focused on single-polymer kinetic models or employed simplified reaction schemes, this study develops an enhanced multistep reaction network that explicitly considers both primary decomposition and secondary cracking pathways, thereby improving the accuracy of product distribution predictions. By integrating this detailed reaction framework with a robust nonlinear regression approach using LSQNONLIN and ODE45 solvers in MATLAB, the study achieved greater accuracy in estimating kinetic parameters than traditional curve-fitting methods. The findings reveal that HDPE exhibits the highest activation energy (222.97 kJ mol(-1)), indicating it is more thermally stable than LDPE (193.44 kJ mol(-1)) and PP (62.16 kJ mol(-1)). One of the highlights of the present work is that lower pyrolysis temperature (400 degrees C) is found to be optimum for liquid yield by reducing secondary cracking, which aligns with the sustainable fuel production principles. The study also emphasizes on the limitations of previous lumped models that overlooked wax decomposition pathways, which are crucial for optimizing the hydrocarbon distribution. Future research should investigate catalytic interventions and reactor design modifications to enhance the product selectivity and scalability. This study offers a more comprehensive kinetic framework for advancing the valorization of plastic waste through pyrolysis, aiding the development of efficient waste-to-fuel conversion strategies.
Keywords: Lumped kinetic modeling; Plastic pyrolysis; Rate constants; Reaction pathways; Secondary cracking reactions; Temperature-dependent product distributions

Reaction kinetics for dehydrogenation of decahydroquinoline to quinoline for hydrogen generation - Bagwan, Farahanaz M.; Dadkar, Sarthak S.; Kinage, Anil K.; Vasireddy, Satyam Naidu (Chemical Engineering & Technology, 2026)
Catalytic dehydrogenation of decahydroquinoline (DHQ) to quinoline is a promising pathway for hydrogen release in liquid organic hydrogen carrier systems. In this work, solvent-free DHQ dehydrogenation over Pd/Al2O3 is systematically investigated to evaluate hydrogen release performance and reaction kinetics. High DHQ conversion (83.9%) and degree of dehydrogenation (82.7%) are achieved at optimal reaction conditions. A power-law kinetic model based on a simplified reaction mechanism is developed and simulated using a Markov Chain Monte Carlo (MCMC) approach for estimation of rate constants and validation of concentration profiles with experimental data. The apparent activation energies are determined to be 45.85 kJ/mol for DHQ to 5,6,7,8-tetrahydroquinoline (bz-THQ) and 185.43 kJ/mol for bz-THQ to quinoline formation, identifying latter as the rate-limiting step. This framework provides mechanistic insight and supports the potential of DHQ as an efficient hydrogen carrier.
Keywords: Decahydroquinoline (DHQ); degree of dehydrogenation; Dehydrogenation; rate-limiting step; Reaction kinetics; Weisz-Prater criterion